2019
DOI: 10.31501/rbcm.v27i1.7525
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Regulação Exteroceptiva E Interoceptiva Do Equilíbrio Corporal De Idosos Ativos.

Abstract: Em se tratando da população idosa, a avaliação do equilíbrio corporal é importante, pois possibilita a predição do risco de queda. Considerando que o equilíbrio sobrevém de diferentes fatores, sua avaliação exige a aplicação de diferentes instrumentos, o que traz vantagens e desvantagens para a avaliação. Os testes geralmente utilizados à detectação de alterações do equilíbrio estático e dinâmico não permitem o exame de sua regulação exteroceptiva e interoceptiva. O objetivo do presente estudo foi avaliar o eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Although the results point out that Pilates is not the most effective intervention to control blood pressure, glycaemia [57], and the sensory regulation of static or dynamic balance [58], we could not, however, fail to highlight the positive effects of Pilates on strength [48,53,59], improvements in the functional capacity and mobility of the elderly [52,59,60], and in psychological variables such as self-resilience [49] and wellbeing [50]. Furthermore, improvements in haemodynamic behaviour [56] and salivary S-IgA [51] were also mentioned in the systematic review of the studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the results point out that Pilates is not the most effective intervention to control blood pressure, glycaemia [57], and the sensory regulation of static or dynamic balance [58], we could not, however, fail to highlight the positive effects of Pilates on strength [48,53,59], improvements in the functional capacity and mobility of the elderly [52,59,60], and in psychological variables such as self-resilience [49] and wellbeing [50]. Furthermore, improvements in haemodynamic behaviour [56] and salivary S-IgA [51] were also mentioned in the systematic review of the studies.…”
Section: Discussionmentioning
confidence: 89%
“…This section included 14 studies with similar benefits being reported, despite different methodologies used. Two studies show that Pilates is not the most effective intervention to control blood pressure, glycaemia [57], and the sensory regulation of static or dynamic balance [58]. The remaining studies, however, report gains in strength [48,53,59] and improvements in the functional capacity and mobility of the elderly [52,59,60].…”
Section: Observational or Non-randomized Studiesmentioning
confidence: 99%
“…quando os dados que avalia são a partir de 11 segundos de realização. Quanto ao teste de alcance funcional (TAF), seu papel é determinar a capacidade do idoso de se deslocar no limite de estabilidade anterior de seu tronco, onde deslocamentos inferiores a 15 centímetros sinalizam risco eminente de quedas 9 .…”
Section: Metodologiaunclassified
“…Human aging process triggers a set of changes in the organism, especially in posture alignment and dynamic balance. Posture alignment involves stability and body orientation in space, while dynamic balance is an essential component for postural control, maintaining older adults in the desired body position and preventing falls (Sant'Anna et al, 2019;Pinzón Ríos, 2019;Nascimento et al, 2019;Horak, 2006).…”
Section: Introductionmentioning
confidence: 99%